The effect of beta-adrenoceptor antagonists on the pharmacokinetics and pharmacodynamics of warfarin after a single dose. - Bax, N D (1984)
The effects of three beta-adrenoceptor antagonists (propranolol, metoprolol and atenolol) on the serum kinetics and pharmacodynamics of warfarin given in a single oral dose (15 mg) were studied in six normal subjects. At the same degree of beta-adrenoceptor blockade, as assessed by the decrease of exercise tachycardia, propranolol increased the area under the serum warfarin concentration time curve (AUC) by 16.3 +/- 14.2 s.d.% (P less than 0.01) and the maximum serum warfarin concentration by 23.0 +/- 14.3 s.d.% (P less than 0.001). Atenolol increased the maximum serum warfarin concentration by 12.5 +/- 12.3% s.d. (P less than 0.05) but was without effect on warfarin AUC. Metoprolol had no effect on warfarin kinetics. The extent of changes in the prothrombin time and the plasma clotting Factor VII activity caused by warfarin were not altered by any of the beta-adrenoceptor antagonists.